2010
DOI: 10.1258/rsmsmj.55.3.26
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Care of New European Migrants in Scotland: an audit of antenatal care, obstetric outcomes and communication

Abstract: Full compliance with antenatal and interpretation standards was not achieved for this population. ITS was most commonly used to meet the needs of healthcare professionals, rather than as a routine. While there were no significant differences in maternity outcomes, poor communication did affect care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 8 publications
(9 reference statements)
1
42
0
Order By: Relevance
“…It is likely that this relationship may be partially explained by socio‐economic status18 and immigration status,24 which were either not fully adjusted for or not available in this study.…”
Section: Discussionmentioning
confidence: 96%
“…It is likely that this relationship may be partially explained by socio‐economic status18 and immigration status,24 which were either not fully adjusted for or not available in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Differences in rates of medical procedures between migrant and host-country women were found in some countries (Diani, Zanconato, Foschi, Turinetto, & Franchi, 2003;Ibison, 2005;Ma & Bauman, 1996). Pain management, length of stay, and deliveries requiring intervention were found in migrants compared to host nationals and suggest indicators for measuring health care equity in the delivery theme for this population (Bray, Gorman, Dundas, & Sim, 2010;Hayes, Enohumah, & McCaul, 2011). Other studies, reporting on user-perceived measures such as satisfaction with care and feeling treated with respect by health care providers noted both similarities and differences between these groups (Ameh & van den Broek, 2008;Small, Rice, Yelland, & Lumley, 1999;Small, Yelland, Lumley, Brown, & Liamputtong, 2002).…”
Section: Equity In Access To Health Care Servicesmentioning
confidence: 93%
“…46 In the UK, a high proportion of unbooked or late booking mothers are immigrants. 16,47 In the Rotunda Hospital an analysis of 1954 migrant women who delivered in 2002 revealed that 20% did not attend any antenatal care and a further 20% attended for the first time in the 28 days before delivery. 48 Immigrants in the Netherlands are more likely to commence antenatal care late.…”
Section: Contributory Factors To Poorer Outcomesmentioning
confidence: 99%
“…29 In a recent Scottish study, interpretation services were not used in over one-third of those patients who were identified to require it. 16 The provision of professional interpretation services for all pregnant patients who do not speak English is consequently a high priority. 31 Useful aides to communication for medical staff include foreign language translation information cards for commonly performed procedures and phrase and picture cards such as those available on the Obstetric Anaesthesia Association website (http:// www.oaa-anaes.ac.uk).…”
Section: Communication and Translation Servicesmentioning
confidence: 99%
See 1 more Smart Citation